The ethical formation of undergraduate students in pedagogy in times of “gender ideology”: a cross-sectional study using the Defining Issues Test-2 (DIT-2) - da Silva, Matheus Estevão Ferreira [UNESP]; de Morais, Alessandra [UNESP]; Brabo, Tânia Suely Antonelli Marcelino [UNESP] (FapUNIFESP (SciELO), 2024)
In this article, the result of research that focused on the ethical dimension of the pedagogue’s work with gender and sexuality issues at school, the objective was to analyze the ethical formation, from the point of view of moral development, of undergraduate students in Pedagogy at a public University in São Paulo. The sample was composed of 165 subjects enrolled in the initial and final years of the course that set the research. To measure their ethical background, Kohlbergian and neo-Kohlbergian approaches to moral development and the Defining Issues Test 2 (DIT-2) were used. The results showed that the ethical formation of undergraduate students remains stagnant and even indicates a certain regression throughout the course. In addition, the low performance of the participants was strongly related to their religious bond, implying that the bond and the religious formation can delegitimize and curb their ethical formation.
Formación ética de estudiantes de pregrado en pedagogía en tiempos de “ideología de género”: un estudio transversal utilizando el Defining Issues Test-2 (DIT-2)
Formação ética de graduandos/as em Pedagogia em tempos de “ideologia de gênero”: um estudo transversal utilizando o Defining Issues Test-2 (DIT-2)
Keywords: Desarrollo Moral; Desenvolvimento Moral; DIT-2; Ethics; Formación Inicial de Profesores; Formação Inicial Docente; Initial Teacher Formation; Moral Development; Pedagogia; Pedagogy; Pedagogía; Ética